Research on the growth of kids in goat breeding with good flock management - Elmaz Özkan (Review on agriculture and rural development, 2021)
This study was carried out to demonstrate the effect of "Good Flock Management" on the growth characteristics of goats. Studies conducted in the province of Burdur in Turkey under "Focused District Development Project". Goat flocks were in Beşkavak village which was selected as a model village, were used in the study. The study was carried out in 2019 in two goat flocks. The birth weights of the male and female kids were determined as 4.04 kg and 3.58 kg and 4.09 kg and 3.52 kg respectively for the first and second flock. On the90th day of the first and second flock, the live weight values of male and female kids were determined as 17.68 kg and 14.17 kg and 19.81kg and 16.94 kg respectively.  Single born kids’ live weight value on the 90th day in flock 1 determined as 15.85 kg.